Monte Carlo Simulation of Supercritical Carbon Dioxide Adsorption in Carbon Slit Pores - Gu, S.; Gao, B.; Teng, L.; Li, Y.; Fan, Chunyan; Iglauer, S.; Zhang, D.; Ye, X. (American Chemical Society, 2017)
© 2017 American Chemical Society. CO 2 adsorption on carbon is a CO 2 geo-storage mechanism, and a potential technique for CO 2 removal from flue gas or pressurized fuel gas streams produced from hydrocarbon reservoirs (which frequently contain CO 2 , sometimes at very high concentrations). However, the detailed mechanism of precisely how CO 2 is adsorbed on the carbon surface is only poorly understood. We thus simulated supercritical CO 2 adsorption in carbon slit pores at the molecular level by Grand Canonical Monte Carlo calculations. Adsorption isotherms and microscopic structural properties were examined for different pore widths, pressures, and temperatures. Our results demonstrate that the excess adsorption density isotherm of supercritical CO 2 in a carbon slit pore has a maximum value, and it is not a monotonically increasing function of pressure. However, supercritical CO 2 cannot be effectively adsorbed at very high temperatures (=850 K) as the excess adsorption density is extremely small. Mechanistically, multiadsorption layers were observed in large slit pores (pore width = 20 Å); these were defined as contact layers, inner layers, and free layers, respectively. Finally, the optimum pore widths for supercritical CO 2 adsorption under different conditions were determined, which is vital for optimizing adsorbent and CO 2 geo-storage efficiency.